(untitled) - Ward, Ian (London, 1999)
This work offers an analysis of constitutional law, examining Shakespeare's plays as legal texts. Professor Ward uses the plays as a starting point to investigate the development of constitutional ideas such as sovereignty, commonwealth, conscience and moral law, and the art of government. In the developing area of law and literature, this book examines how Shakespeare's work offers a rich source of textual material on legal subjects.
Keywords: Law and literature,Law and literature,Law in literature,Luật và văn học,Luật và văn học,Luật trong văn học; History,History,Lịch sử,Lịch sử; 16th century,17th century,Thế kỷ 17,Thế kỷ 16